Business Profitability and Minimum Capital Adequacy Ratio of Regional Development Banks in The Middle of The Covid19 Pandemic Crisis - Iswadi Ayub; Syamsu Alam; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
The purpose of this study is to analyze the effect of return on assets (ROA) on the capital adequacy ratio (CAR); To analyze the effect of Net interest margin (NIM) on the capital adequacy ratio (CAR); To analyze the effect of operating costs versus income (BoPo) on the capital adequacy ratio (CAR); and to analyze the influence of the most dominant ROA, NIM, or BoPo on the capital adequacy ratio (CAR). In this study, the authors conducted an analysis to see the effect of the profitability ratios (RoA, NIM, and BoPo) on the capital ratio of BPD banks in Indonesia during the Covid19 pandemic crisis (2019-2020). The data in the form of financial ratios is processed using the IBM SPSS program with multiple regression analysis techniques. The results showed that the ROA variable had no significant positive effect on the CAR variable. This means that the high and low ROA does not always affect the CAR, the NIM variable does not have a significant positive effect on the CAR variable. This means that the high and low NIM does not always affect the CAR, the BOPO variable has a significant negative effect on the CAR variable. This means that the higher the BOPO, the lower the CAR, and vice versa, the lower the BOPO will increase the CAR. The BOPO shows the dominant influence on the CAR variable.